2017
DOI: 10.7324/japs.2017.70926
|View full text |Cite
|
Sign up to set email alerts
|

Antifibrotic candidates of Selenium nanoparticles and selenium in the experimental model

Abstract: This research was designed to compare the efficacy of selenium in nanoscale (SeNPs) with its free form (Se) against liver fibrosis induced by thioacetamide (TAA) in rats. In a completely randomized design, 60 adult female rats were distributed as: Group (1) control (received saline) and other three groups received TAA to induce liver fibrosis (100 mg/kg b.wt of three times a week for 6 weeks). Fifteen rats were termed TAA (Group 2). Rats in group (3) were simultaneously administered SeNPs (0.48 mg/kg/b.wt) ora… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(2 citation statements)
references
References 20 publications
0
2
0
Order By: Relevance
“…Hirst and coworkers also investigated CeO 2 NP (3–5 nm) and CCl 4 -induced liver fibrosis in mice and found that CeO 2 NP reduced oxidative stress damage markers to levels comparable to N -acetylcysteine [ 19 ]. Other NP types, such as TiO 2 NP, silicon dioxide NP [ 31 ], zinc oxide NP [ 32 ] and selenium NP [ 33 ], have previously been shown to inhibit liver fibrosis, demonstrating that NPs are indeed capable of attenuating the fibrotic liver phenotype.…”
Section: Introductionmentioning
confidence: 99%
“…Hirst and coworkers also investigated CeO 2 NP (3–5 nm) and CCl 4 -induced liver fibrosis in mice and found that CeO 2 NP reduced oxidative stress damage markers to levels comparable to N -acetylcysteine [ 19 ]. Other NP types, such as TiO 2 NP, silicon dioxide NP [ 31 ], zinc oxide NP [ 32 ] and selenium NP [ 33 ], have previously been shown to inhibit liver fibrosis, demonstrating that NPs are indeed capable of attenuating the fibrotic liver phenotype.…”
Section: Introductionmentioning
confidence: 99%
“…The findings revealed that SeNPs and Se intake reduced the action of liver enzymes, oxidative stress markers, and inflammatory mediators while increasing the activity of enzymes as compared to the thioacetamide group. The reduction of oxidative stress and inflammation could be the processes via which SeNPs or Se exert antifibrotic effects [ 39 ].…”
Section: Role Of Senps In Several Diseasesmentioning
confidence: 99%